Adaptasi Tanaman Kedelai Terhadap Intensitas Cahaya Rendah : Karakter Daun untuk Efisiensi Penangkapan Cahaya - La Muhuria; Kartika Ning Tyas; Nurul Khumaida; , Trikoesoemaningtyas; Didy Sopandie (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
This research was conducted to identify some leaf characters related to light capture efficiency. It used split plot design with sub plot nested at the main plot. The main plot was light intensity consisted of two levels: I100 = light intensity 100% and I50 = light intensity 50%, while the sub plot was soybean genotype consisted of G1 = Pangrango, G2 = Ceneng, G3 = Godek, and G4 = Slamet. Leaf characters measured were : leaf total area, specific leaf area, trifoliate leaf area, leaf hairs (trichome) density, leaf thickness, length of palisade, chlorophylls content (chlorophyll a, b, and ratio a/b), and the greenness intensity. The result of research indicated that Ceneng has lower total leaf area, higher specific and trifoliate leaf area, less leaf hair density, thinner leaf, shorter palisade, higher greenness intensity, higher chlorophyll content (a and b), and also lower ratio chlorophyll a/b. Key words: Light capture efficiency, light intensity, tolerant genotype, sensitive genotype, soybean